3D Printed High‐Strength Supramolecular Polymer Hydrogel‐Cushioned Radially and Circumferentially Oriented Meniscus Substitute. (2nd March 2022) - Zhang, Qian; Xu, Ziyang; Zhang, Xiaoping; Liu, Changjun; Yang, Rong; Sun, Yage; Zhang, Yahan; Liu, Wenguang
Abstract: Developing a meniscal replacement with reliable long‐term mechanical and functional support has faced a grand challenge due to difficulty in recapitulating the anisotropic microarchitecture and modulus. Herein, a high‐strength supramolecular polymer hydrogel‐cushioned biomimetic structured meniscus replacement is reported for the first time. The radially and circumferentially oriented poly(e‐caprolactone) (PCL) fiber framework is 3D printed to imitate collagen fibers in the native meniscus to provide circumferential tensile supports. Then, hydrogen bonding strengthened anti‐swelling poly( N ‐acryloyl glycinamide) (PNAGA) hydrogel that replicates the function of proteoglycan in resisting axial compressive loads is infused into the 3D printed PCL framework, thus fulfilling a durable energy absorbing and cushion function, which far outperforms the performance of conventional polyacrylamide hydrogel. The PNAGA‐cushioned PCL construct can achieve Young's moduli of 20.15 ± 1.37 MPa in the circumferential direction and 10.43 ± 1.54 MPa in the radial direction, a compressive modulus of 1.11 ± 0.14 MPa as well as a tearing energy of 17.00 ± 2.07 kJ m −2 . This 3D printed PCL‐PNAGA meniscus scaffold is implanted into rabbit knee joints for 12 weeks and in vivo outcome demonstrates the structural stability and efficient protection against wearing of the cartilage, meanwhile ameliorating the development of osteoarthritis. Abstract : A biomimetic structured meniscus replacement is fabricated by 3D printing of stiff radially and circumferentially oriented poly(ε‐caprolactone) (PCL) framework to provide tensile support, followed by infusion of high‐strength supramolecular poly( N ‐acryloyl glycinamide, PNAGA) hydrogel to fulfill a durable energy absorbing and cushion function. The PCL‐PNAGA meniscus substitute can efficiently protect cartilage and ameliorate osteoarthritis in rabbit meniscal removal model 12 weeks post‐operation.